Functional Disruption of the Tomato Putative Ortholog of HAWAIIAN SKIRT Results in Facultative Parthenocarpy, Reduced Fertility and Leaf Morphological Defects - Damayanti, Farida; Lombardo, Fabien; Masuda, Jun-ichiro; Shinozaki, Yoshihito; Ichino, Takuji; Hoshikawa, Ken; Okabe, Yoshihiro; Wang, Ning; Fukuda, Naoya; Ariizumi, Tohru; Ezura, Hiroshi (Frontiers in Plant Science, 2019)
A number of plant microRNAs have been demonstrated to regulate developmental processes by integrating internal and environmental cues. Recently, the Arabidopsis thaliana F-box protein HAWAIIAN SKIRT (HWS) gene has been described for its role in miRNA biogenesis. We have isolated in a forward genetic screen a tomato (Solanum lycopersicum) line mutated in the putative ortholog of HWS. We show that the tomato hws-1 mutant exhibits reduction in leaflet serration, leaflet fusion, some degree of floral organ fusion and alteration in miRNA levels, similarly to the original A. thaliana hws-1 mutant. We also describe novel phenotypes for hws such as facultative parthenocarpy, reduction in fertility and flowering delay. In slhws-1, the parthenocarpy trait is influenced by temperature, with higher parthenocarpy rate in warmer environmental conditions. Conversely, slhws-1 is able to produce seeds when grown in cooler environment. We show that the reduction in seed production in the mutant is mainly due to a defective male function and that the levels of several miRNAs are increased, in accordance with previous HWS studies, accounting for the abnormal leaf and floral phenotypes as well as the altered flowering and fruit development processes. This is the first study of HWS in fleshy fruit plant, providing new insights in the function of this gene in fruit development.